Micro-curricular planning and its influence on the acquisition of english as a second language with the students of 8th, 9th and 10th grades of basic education at colegio nacional mixto Vilcabamba, academic year 2014-2015 - Malla Rengel, Janina Vanessa (2015)
This research work was aimed at establishing the impact of Micro curriculum planning and its influence on English second Language Acquisition in the students 8th, 9th and 10th Years of Basic Education at the Vilcabamba National Public High School and gives suggestions to be included in the programs of Micro Planning Curriculum for English Language Teaching. There were used the scientific, descriptive, analytic- synthetic and explanatory methods, with a sample of 311 students and 4 teachers of the area of English. A survey was conducted for teachers and students to verify hypotheses through logical analysis of the results and descriptive statistics to represent the data in tables and graphs. The results showed that teachers of English at this school know and apply the Micro Planning Curriculum established by the Ministry of Education of Ecuador as a requirement in all teaching process, also it was established that teachers do not consider teaching materials to support their classes. Finally, it is concluded that the curriculum planning is important for teachers to apply English classes and acquire a good of domain language in class